HUBUNGAN SELF CONFIDENCE TERHADAP KEMAMPUAN BERFIKIR KREATIF MATEMATIS SISWA MTs - siti hafsah masfufah; Puput Winarsih; Gida Kadarisma (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This research to find out in depth about the relationship of self confidence to the ability to think creatively mathematically MTs students. The population in this research is MTs in Cimahi City. Instrument in this research in the form of description of ability of mathematical  creative thinking as much as 5 item, and self confidence questionnaire of student. Methods in this research using correlational research  methods. The result of this research shows that there is a correlation (r) value on Person Corellation between self confidence with students’ mathematical creative thinking ability is 0,597**. Form these results show the level of relationships that are classified and indicate the direction of a positive relationship.